Design and Simulation of a QPSK Demodulator Using Discrete Components - Andicho Haryus Wirasapta; Salisa 'Asyarina Ramadhani; Mishi , Salmuna Sajjad; Malik, Zeeshan Hamid (Jurusan Teknik Elektro Universitas Andalas, 2025)
Quadrature Phase Shift Keying (QPSK) is a widely adopted digital modulation technique that encodes two bits of information in each symbol by utilizing four distinct phase states separated by 90 degrees. This approach offers high spectral efficiency, making it especially suitable for modern communication systems that demand robust data transmission with limited bandwidth. This investigation details the design process and LTspice-based simulation of a QPSK demodulator constructed entirely from discrete electronic components. This work addresses a gap in previous research, which has largely relied on integrated circuits or software-based algorithms, by focusing on circuit-level implementation using basic analog and digital components. The demodulator was assembled on a prototype PCB, combining fundamental operational amplifiers, mixers, filters, and digital logic gates to perform the required signal processing functions. The evaluation involved testing the demodulator's ability to accurately recover the transmitted data and its operational stability. Simulation results demonstrated reliable performance across all stages, with the demodulator successfully maintaining phase detection accuracy and reconstructing the original 8-bit test sequence with high fidelity. Under test conditions with a 1 MHz carrier frequency and a data transmission rate of 500 kHz, the recovered signal showed an approximate delay of 4.5 microseconds attributable to the sequential parallel-to-serial conversion process. Despite the delay, the demodulator maintained full symbol-level correlation with the transmitted data stream. These findings confirm that a discrete component-based QPSK demodulator can effectively support reliable digital communication, highlighting its practicality for educational purposes, low-cost prototyping, laboratory training, and preliminary hardware development in the field of wireless and wired communication systems.